2020
DOI: 10.1111/os.12759
|View full text |Cite
|
Sign up to set email alerts
|

Bland–Altman Analysis of Different Radiographic Measurements of the Hallux Valgus Angle and the Intermetatarsal Angle After Distal Osteotomy

Abstract: The aim of the present study was to evaluate commonly used approaches for detection of radiographic angles in hallux valgus deformity patients. Methods: This retrospective study was conducted in patients with hallux valgus deformity at Wangjing Hospital of China Academy of Chinese Medical Sciences from January 2016 to January 2019. The inclusion criteria were: (i) postoperative dorsoplantar weight-bearing radiographs for the feet of patients with the hallux valgus; (ii) patients had been managed with a distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A normal value is under 9 . 22,23 The IMA, like the HVA, can similarly be affected by the measurement method and subjected to potential risk in error. However, studies have shown no improvement in reliability based on experience.…”
Section: Discussionmentioning
confidence: 99%
“…A normal value is under 9 . 22,23 The IMA, like the HVA, can similarly be affected by the measurement method and subjected to potential risk in error. However, studies have shown no improvement in reliability based on experience.…”
Section: Discussionmentioning
confidence: 99%
“…If the difference follows a normal distribution, 95% of the points should be within the mean ± 1.96 SD. This interval is called the 95% LOA [44][45][46].…”
Section: The Consistency and Loa Of The Mir Methods And Adjusted Ultr...mentioning
confidence: 99%
“…We intend to analyze the imaging changes and symptom scores of hallux valgus patients before and 12 months after operation, and comprehensively evaluate the clinical e cacy of DMMO in the treatment of hallux valgus.The imaging evaluation is to take the weight-bearing X-ray positive and lateral view of the foot, and measure and analyze the changes of HVA, IMA and DASA before and 12 months after the operation on the X-ray lm.The imaging angle measurement in this research refers to the paper by DAI [9] .The symptom function score included comparing the VAS score of patients before and after operation and evaluating the overall curative effect according to AOFAS score scale: 90-100 points were excellent, 75-89 points were good, 50-74 points were fair, 50 points were poor [10] . This clinical trial has been registered in China Clinical Trial Registration Center, registration number (ChiCTR2000038668).…”
Section: Exclusion Criteriamentioning
confidence: 99%